PENENTUAN POLA OPERASI BERDASARKAN ANALISIS BEBAN KERJA PEMBANGKIT LISTRIK TENAGA DIESEL DI PULAU GILI IYANG - Susilo, Wiji; Suhariyanto (Rekayasa Sistem Energi dan Manufaktur (ReSEM), 2025)
The Diesel Power Plant (PLTD) on Gili Iyang Island is the only power plant on the island with a capacity of 1,220 kVA, operating in an isolated system or not connected to other power plants. The current peak load is 416 kW, and is supplied by 3 units: Unit 1 of 656 kW, Unit 2 of 160 kW, and Unit 3 of 160 kW. Therefore, if there is a disruption in Unit 1, it leads to rotational blackouts. By observing the number of customers and the consumption of diesel fuel in relation to the energy generated by the diesel engines, the ideal power and operational pattern that can enhance the reliability of the PLTD can be determined. The current contracted number of customers is 1792, with a total power of 1894 kVA, assuming a load factor of 65% and a safety factor of 120%, the ideal PLTD power is obtained as 1500 kVA. In determining the operational pattern, it is divided into 4 patterns considering the generator's load. Patterns 1 to 3 utilize the composition of the existing 3 engines, while Pattern 4 involves an additional engine. Considering the reliability of the generator's operation, Pattern 4 is the most effective with a fuel requirement of 1,599.86 liters per day at a cost of IDR. 2,879.69/kWh